Does caffeine consumption influence postcompetition sleep in professional rugby league athletes? a case study - Caia, J.; Halson, S. L.; Holmberg, P. M.; Kelly, V. G. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To examine the sleep of rugby league athletes the night before and following an evening match and to investigate the association between caffeine intake and sleep on the night of competition.